MANAJEMEN RANTAI PASOK: IMPLEMENTASI DAN EFEKTIVITAS MEDIA SOSIAL DALAM PENGELOLAAN BISNIS RADIO (Studi pada Radio 89.6FM IRadio Jakarta) - Ahmad Mulyana (Universitas Mercu Buana, 2019)
The sustainability of industrial business depends on the ability of organizations to manage the needs and desires of consumers so that the products produced become part of consumer life. The radio broadcast industry in the era of digital technology is threatened no longer able to meet the needs of its listeners because social media has changed the behavior of audiences in consuming radio media. on that basis the radio broadcast industry must adapt to managing radio broadcasts by synergizing the behavior of the use of digital media with radio characters that are personal to the audience so that the radio broadcast industry continues to survive. The purpose of this study was to determine the management of social media and identify the added value it generates to maintain the business continuity of radio broadcast programs, especially Iradio 89.6 FM. The related concept is digital media management, product added value for business continuity. The research method used is a case study with a qualitative approach with the support of data triangulation so that the analysis can meet the validity aspects of the data. The results showed that the management was carried out with a strategy to build emotional bounding audiences through social media by synergizing digital technology with broadcast radio-based programming content. This helps the business continuity of IRadio 89.6 FM significantly. The existence of digital media for the radio industry is as a complement rather than as a competitor and digital media makes radio easier to access from various areas